Increasing Accuracy of Correspondences in Stereo Vision by Implementing Image Registering Technique - Enesi , Indrit; Kuqi , Anduel (International Journal of Intelligent Systems and Applications in Engineering, 2023)
3D reconstruction on stereo vision is widely used mainly for measuring distances of objects in a scene or sizes of the object. It is based on the triangulation of point correspondences in stereo images. The accuracy of point correspondences as well their number has great impact in the performance of 3D reconstruction of the object in a scene. In many cases stereo images are obtained by handheld cameras, with same parameters or not. The vertical camera axes are assumed to be parallel, but usually they are approximately parallel or not parallel, obtained stereo images are rotated related to each other. The paper considers the pixel correspondences in case where cameras have different parameters, and the vertical axes of stereo images create an angle between them. Images are first aligned according to each other by a transformation function defined by control points. Point correspondences between reference and registered image are defined, and their similarity is calculated based on respective normalized descriptive vector. Statistics about correspondences in registered images is compared with the ones in rotated images. Experimental results show that accuracy of correspondences is increased.